2014
DOI: 10.1007/s12028-014-9964-0
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Magnesium Sulfate for Aneurysmal Subarachnoid Hemorrhage: A Systematic Review and Meta-analysis

Abstract: Delayed cerebral ischemia following aneurysmal subarachnoid hemorrhage is a cause of considerable morbidity and mortality. Magnesium sulfate has been proposed as a prophylactic intervention for angiographic vasospasm and to improve clinical outcomes. A systematic review was conducted to determine the evidence for the prophylactic use of magnesium sulfate in aneurysmal subarachnoid hemorrhage. Medline, Embase, Cochrane library, clinicaltrials.gov, and controlled-trials.com were searched with a comprehensive sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Funnel plots were used to analyze whether publication bias exists in the included studies. Metaanalysis was conducted using Review Manager 5.1 software (Cochrane collaboration, Copenhagen, Denmark) 17 . The Quality in Prognostic Studies (QUIPS) tool was used for assessment of study reliability 18 .…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…Funnel plots were used to analyze whether publication bias exists in the included studies. Metaanalysis was conducted using Review Manager 5.1 software (Cochrane collaboration, Copenhagen, Denmark) 17 . The Quality in Prognostic Studies (QUIPS) tool was used for assessment of study reliability 18 .…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…Cerebral vasospasm is a difficult pathological entity to treat or to deal with it and also in the literature are a lot of studies and trials about the controversies concerning the prevention and the treatment of the cerebral vasospasm that can occur after subarachnoidian hemorrhage (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that routine administration could not be recommended [46]. Nevertheless, in a recent metaanalysis, DCI was the only outcome with a statistically significant effect favoring magnesium treatment [47]. This meta-analysis also concluded that prophylactic use of magnesium is not supported by current evidence, as functional outcome was not improved.…”
Section: Subarachnoidal Hemorrhagementioning
confidence: 95%